PERTANGGUNGJAWABAN BANK TERHADAP NASABAH KORBAN KEJAHATAN ITE DI BIDANG PERBANKAN - Yudanto, Yudanto; Surbakti, Natangsa; Yuspin, Wardah (Universitas Muhammadiyah Ponorogo, 2024)
The recent rise in ITE crimes in the banking sector has given rise to new problems, both legally and economically. These crimes often involve resource users, infrastructure, and customer identities. As a result, in terms of implementing criminal law, especially banking and financial services companies must bear responsibility for their customers' losses. The importance of bank accountability towards its customers who are victims of ITE crimes from a criminal law perspective is the objective discussed in this research. This legal research refers to positive legal norms in accordance with the hierarchy of existing laws and regulations, legal principles, legal doctrine, as well as other literature relating to Bank responsibility for crimes in criminal law. The results of the analysis from this research show the importance of protecting bank customers by banks and that there have been efforts made by the Indonesian banking industry to empower and protect consumers with the banking criminal regulations in Law no. 10 of 1998 which is mentioned in detail therein.